Controlled-environment agriculture for an urbanised world? A comparative analysis of the innovation systems in London, Nairobi and Singapore - Victoria Dietze; Amna Alhashemi; Peter H. Feindt (Food Security, 2024)
Abstract Multiple crises and challenges in the food sector are driving a rising need for innovative food production methods that could provide a growing urban population with high-quality, sustainable and healthy food while strengthening the resilience of food systems. Controlled-environment agriculture (CEA) in urban areas has been proposed as one possible pathway to address these demands. Despite its~various potential~benefits, CEA is still in a conceptual or experimental stage and there has been less research that focuses on the specificities of urban areas where it could be implemented. Using the Urban Food Production Innovation System (UFoPrInS) concept, this paper analyses the urban contexts and enabling and impeding factors for implementing CEA in three contrasting locations: London, Nairobi and Singapore. Based on document analysis and semi-structured expert interviews, our findings show that Singapore is a favourable location because public policies support the implementation of CEA to reduce food import dependency and enhance the resilience of food supply. In London, high food import dependency is increasingly seen as problematic, but the implementation of CEA has been hampered by other policy priorities. In Nairobi, where over half of the population lives in informal settlements without adequate food, water and sanitation, CEA is unlikely to make an economically efficient contribution to food security. We conclude that the implementation of CEA might be suitable in locations with ample capital and knowledge, stable political, social, and infrastructure conditions, and limited space, where value can be linked to hospitality and tourism, supported by positive pricing for resource savings.
Keywords: 330; Urban food production systems; Resource-efficient food production; Innovation system; Institutional framework; Systemic problems; Case study analysis